Views of Urban and Suburban Residents of Lahore Regarding Environment and Its Association with Reported Frequency of Common Ailments - Akmal, Asma; Laeeque, Bisma; Ahsan, Rakhshan; Fatima, Sheza (Nurture, 2020)
This study was conducted to ascertain the health status of people living in urban and suburban areas of Lahore. It determined the level of variance and correlation between the health status of people living in the aforementioned areas with its environment. A quantitative cross-sectional survey was conducted to gather the results. Data was collected with the help of a questionnaire based on a five-point scale. One way ANOVA was conducted to test the hypothesis and the results revealed that people living in suburban areas are healthier (p< .005) in comparison to people living in urban areas. The Pearson correlation results (.272) revealed that a positive direct correlation exists between the health of residents and the environment in which they live.